Detariffing-Whether Profitable to Insurer or Insured - Natarajan, Sangeetha; Poornima, S (Journal of Commerce and Trade, 2008)
In this era of Globalization and Liberalization along with the paradigmatic shift in the development strategy, the Insurance sector which remained relatively untouched by the reforms also become the part of it and is not exempted. In this way IRDA has requested the insurance companies to initiate steps in order to ensure the transition from tariff regime to detariff regime. The present paper is an attempt to introspect the problems and prospects of both Insurer and Insured with respect to Detariffing .The Perception of 120 Agents and 200 Customers were found using self structured questionnaire and was analyzed using tools like Simple Percentage. Central Tendency ( Mean, Weighted mean ,Standard deviation ) and was ranked in their order of preference. Based on findings a snapshot of SWOT Analysis was drawn showing the leveraging strength, opportunities to be exploited, rectifying weaknesses and threats to be overcome , to standout as a winner in the liberalized economy.